ANALISIS YURIDIS PERTANGGUNGJAWABAN PIDANA KORPORASI DALAM KASUS PENCEMARAN AIR - Firmansyah, Asram A.T. Jadda, Uly Anggara (Madani Legal Review, 2021)
This research aims to know the juridical analysis of corporate criminal liability in the case of river water pollution and barriers to the application of criminal sanctions against corporate criminal liability in the case of river water pollution Data analysis is done by using the Deskriftif-qualitative analysis. Findings gained from this study include, in law No. 32 of 2009 on environmental protection and management there is no coformity in the policy phase of the application, so in the future it needs to be further affirmed again and Barriers to implementation of criminal sanctions on corporate criminal liability in the case of river water pollution a criminal act committed to environmental pollution is very difficult to know. So in the application of criminal sanctions against corporate criminal liability suffered some obstacles in terms of relatively complex substance, environmental law enforcement structures are still not professional, public awareness of law and facilities that support law enforcement are not optimal.